PRMT1‐mediated arginine methylation promotes YAP activation and hepatocellular carcinoma proliferation - Jian Yu; Beibei Yu; Zushun Peng; Jianfeng Zhang; Juhui Sun; Bo Yang; Liushiyang Xu; De Luo (FEBS Open Bio)
The activity of Hippo signaling is commonly dysregulated in various human malignancies, including hepatocellular carcinoma (HCC). YAP, the key effector of Hippo pathway, is regulated through several posttranslational modifications. However, the mechanism by which YAP is regulated by arginine methylation remains unknown. In this study, immunoprecipitation and mass spectrometry were used to identify the arginine methylation site of YAP in HCC cells. The transcriptional activity of YAP and TEAD were further characterized by real‐time qPCR and immunofluorescence assay, and a subcutaneous and orthotopic tumor mouse model was used to assess the effect of PRMT1‐knockdown on HCC tumor growth. The result of mass spectrometry analysis identified that YAP was methylated at arginine 124. Moreover, we found that arginine methyltransferase PRMT1 interacted with YAP to mediate its arginine methylation, thus inhibited YAP phosphorylation and promoted YAP activity in the nucleus. PRMT1 was up‐regulated in HCC tissues and positively associated with the expressions of YAP target genes. Silencing PRMT1 in HCC cells inhibited cell proliferation and tumor growth, while PRMT1‐overexpression promoted HCC growth through YAP methylation. Our study reveals that PRMT1‐mediated arginine methylation at R124 is mutually exclusive with YAP S127 phosphorylation, thereby facilitating YAP activity in the nucleus and promoting tumorigenesis in HCC.